The effect of 10 Hz transcranial alternating current stimulation (tACS) on corticomuscular coherence - Wach, Claudia; Krause, Vanessa; Moliadze, Vera; Paulus, Walter; Schnitzler, Alfons; Pollok, Bettina (Frontiers in Human Neuroscience, 2013)
Synchronous oscillatory activity at alpha (8-12 Hz), beta (13-30 Hz), and gamma (30-90 Hz) fre-quencies is assumed to play a key role for motor control. Corticomuscular coherence (CMC) represents an established measure of the pyramidal system’s integrity. Transcranial alternating current stimulation (tACS) offers the possibility to modulate ongoing oscillatory activity. Behaviourally, 20 Hz tACS in healthy subjects has been shown to result in movement slowing. However, the neurophysiological changes underlying these effects are not entirely understood yet. The present study aimed at ascertaining the effects of tACS at 10 and 20 Hz in healthy subjects on CMC and local power of the primary sensorimotor cortex. Neuromagnetic activity was recorded during isometric contraction before and at two time points (2-10 min and 30-38 min) after tACS of the left primary motor cortex (M1), using a 306 channel whole head magnetoencephalo-graphy (MEG) system. Additionally, electromyography (EMG) of the right extensor digitorum communis (EDC) muscle was measured. TACS was applied at 10 and 20 Hz, respectively, for 10 min at 1 mA. Sham stimulation served as control condition. The data suggest that 10 Hz tACS significantly reduced low gamma band CMC during isometric contraction. This implies that tACS does not necessarily cause effects at stimulation frequency. Rather, the findings suggest cross-frequency interplay between alpha and low gamma band activity modulating functional interaction between motor cortex and muscle.